1988
DOI: 10.1029/jd093id12p15889
|View full text |Cite
|
Sign up to set email alerts
|

Reaction probability of N2O5 on aqueous aerosols

Abstract: The reaction probability, γ, of N2O5 (to form HNO3) with monodisperse NH3/H2SO4/H2O aerosols has been measured in a flow tube reactor at atmospheric pressure. Experiments were performed at temperatures of 274 and 293 K and at relative humidities of 1–76%. It appears that the presence of a liquid phase is necessary for reaction. With NH4HSO4 aerosol, γ values are nonzero, even below the deliquescence point of the pure salt, and show a gradual increase with increasing relative humidity up to constant values of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
257
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(283 citation statements)
references
References 39 publications
(30 reference statements)
20
257
6
Order By: Relevance
“…The weak signals typically observed for surface-adsorbed species using ATR-FTIR required the use of higher concentrations than found in the atmosphere. However, ionization of N 2 O 5 on surfaces is expected to be operational at lower concentrations as well (19,20 …”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The weak signals typically observed for surface-adsorbed species using ATR-FTIR required the use of higher concentrations than found in the atmosphere. However, ionization of N 2 O 5 on surfaces is expected to be operational at lower concentrations as well (19,20 …”
Section: Nomentioning
confidence: 99%
“…In the case of N 2 O 5 , autoionization to NO 2 ϩ NO 3 Ϫ has also been proposed as a key intermediate step (19,20), and rapid reaction with water also occurs, forming nitric acid:…”
mentioning
confidence: 99%
“…The applied particle-gas partitioning depends on temperature and humidity. As in ISORROPIA, under dry and warm conditions the equilibrium shifts toward the gas phase (Nenes et al, 1998). By using the equilibrium approach of Mozurkewich (1993), the partitioning scheme was comparable to Galperin and Sofiev (1998).…”
Section: The Model System Cosmo-muscatmentioning
confidence: 64%
“…Several techniques could be employed to measure γ N 2 O 5 on the surface of different aqueous solutions (Hallquist et al, 2000;Robinson et al, 1997;Hu and Abbatt, 1997;Behnke et al, 1997;Fenter et al, 1996;Van Doren et al, 1990;Mozurkewich and Calvert, 1988). It was reported that the typical values for γ N 2 O 5 are on the order of 10 −2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation